The effects of oil supply and demand shocks on U.S. consumer Sentiment - Jochen H. F. Güntner; Katharina Linsbauer (Johannes Kepler University of Linz, Department of Economics, 2016)
This paper investigates how the University of Michigan's Index of Consumer Sentiment (ICS) - a survey measure of U.S. households' expectations about current and future economic conditions - responds to structural oil supply and demand shocks. We find that the response to an observed increase in the real price of crude oil depends on the underlying reason. While oil supply shocks have little effect on the ICS, other oil demand shocks such as a precautionary demand shock, for example, have a statistically significant negative impact over a two-year horizon. The effect of aggregate demand shocks associated with the global business cycle is positive in the first few months and negative thereafter. Considering the responses of ICS sub-indices and more specific survey questions, we find that expectations about higher future inflation and the associated reduction of real household income as well as a deterioration of perceived vehicle and house buying conditions are the main transmission channels of aggregate demand and other oil demand shocks. Oil shocks also affect consumers' satisfaction with U.S. economic policy.
Keywords: C32; E30; N50; Q41; 330; Consumer sentiment; Oil price shocks; Structural VAR estimation; Transmission channels